(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Stefano Rodotà was a frontier man. On the border between private law and constitutional law, on the border between law and politics and between intellectual research and institutional commitment. The intellectual path of Rodotà has developed from the critique of the property and the anthropological model of individualism owned by the research on humans, moving towards new frontiers, concentrating each time on unprecedented themes and problems: from the web, to privacy to the tragic cases of bio-law and bioethics. The red thread of his research however comes in the reconfiguration of the concepts and legal categories in a constitutionally oriented way, to give centrality to the person and his rights.